1, 2, 5‐Chalcogenadiazole‐Annulated Tripyrazinoporphyrazines: Synthesis, Spectral Characteristics, and Influence of the Heavy Atom Effect on Their Photophysical Properties. Issue 3 (11th December 2014) - Svec, Jan; Zimcik, Petr; Novakova, Lucie; Rakitin, Oleg A.; Amelichev, Stanislav A.; Stuzhin, Pavel A.; Novakova, Veronika
Abstract: A series of low‐symmetry Zn II, Mg II, and metal‐free porphyrazine derivatives with one 1, 2, 5‐chalcogenadiazole ring (with S, Se or Te) and three pyrazines bearing tert ‐butylsulfanyls were synthesized. The absorption maxima of Zn II complexes lay at 660, 674, and 707 nm for S, Se, and Te, respectively, indicating increasing contribution of the 1, 2, 5‐chalcogenadiazole rings to the π‐electronic system. Photophysical studies revealed that introduction of Se as a chalcogen and Zn II as a central metal causes an increase in the singlet oxygen quantum yield, reaching a value of 0.81, whereas the combination of S and Mg II gives only 0.39. This takes place on the account of the fluorescence quantum yields that differ significantly from 0.072 (Zn II +Se) to 0.51 (Mg II +S). These results demonstrated the two‐dimensional heavy atom effect combining the role of the chalcogen (first dimension) as well as the central metal (second dimension). Attempts to prepare oxygen‐containing isologues led to the formation of an unexpected side product. Abstract : The effect of the introduction of different chalcogendiazole rings into porphyrazine analogues is discussed from the point of view of the Q‐band position, quantum yields of fluorescence emission, and singlet oxygen production. The successful synthesis of the target low‐symmetry zinc, magnesium, and metal‐free macrocycles is described. The formation of an unexpected product is also noted.